RNA‐sequencing analysis reveals the hepatotoxic mechanism of perfluoroalkyl alternatives, HFPO2 and HFPO4, following exposure in mice. Issue 4 (24th August 2016) - Wang, Jianshe; Wang, Xiaoyang; Sheng, Nan; Zhou, Xiujuan; Cui, Ruina; Zhang, Hongxia; Dai, Jiayin
Abstract: The toxicological impact of traditional perfluoroalkyl chemicals has led to the elimination and restriction of these substances. However, many novel perfluoroalkyl alternatives remain unregulated and little is known about their potential effects on environmental and human health. Daily administration of two alternative perfluoroalkyl substances, HFPO2 and HFPO4 (1 mg kg −1 body weight), for 28 days resulted in hepatomegaly and hepatic histopathological injury in mice, particularly in the HFPO4 group. We generated and compared high‐throughput RNA‐sequencing data from hepatic tissues in control and treatment group mice to clarify the mechanism of HFPO2 and HFPO4 hepatotoxicity. We identified 146 (101 upregulated, 45 downregulated) and 1295 (716 upregulated, 579 downregulated) hepatic transcripts that exhibited statistically significant changes (fold change ≥2 or ≤0.5, false discovery rate < 0.05) after HFPO2 and HFPO4 treatment, respectively. Among them, 111 (82 upregulated, 29 downregulated) transcripts were changed in both groups, and lipid metabolism associated genes were dominant. Thus, similar to their popular predecessors, HFPO2 and HFPO4 exposure exerted hepatic effects, including hepatomegaly and injury, and altered lipid metabolism gene levels in the liver, though HFPO4 exerted greater hepatotoxicity than HFPO2. The unregulated use of these emerging perfluoroalkyl alternatives may affect environmental and human health, and their biological effects need further exploration. Copyright © 2016 John Wiley & Sons, Ltd. Abstract : Daily administration of two alternative perfluoroalkyl chemicals, HFPO2 and HFPO4 resulted in hepatomegaly and hepatic histopathological injury in mice. Using high‐throughput RNA‐Sequencing, we identified transcripts that showed significantly altered levels in the liver after HFPO2 and HFPO4 treatment. Among them, lipid metabolism associated genes were dominant. The result showed that HFPO2 and HFPO4 exerted hepatotoxic effects similar to their popular predecessors. The unregulated use of these emerging perfluoroalkyl alternatives may impact environmental and human health, and their biological effects need further exploration.